A Psychological Perspective on Curriculum Implementation: Redesigning Teacher Acceptability - Adi Prehanto; Zamzami Zainuddin; Asep Nuryadin; Asep Herry Hernawan; Thiana Nurrusakinah (FKIP Universitas Lampung, 2026)
This study aimed to develop, validate, and evaluate curriculum implementation from the perspective of field practice by examining teachers’ acceptability of curriculum change as a psychological phenomenon. Guided by Sekhon’s theoretical framework of acceptability, this study redesigned acceptability indicators to reflect teachers’ characteristics in authentic school contexts. A mutually adaptive evaluation model was employed to capture the dynamic interaction between curriculum policy and classroom practice. Using a quantitative correlational design, data were collected from 413 elementary school teachers in West Java Province, Indonesia, selected through convenience sampling based on curriculum type, teaching experience, and professional status. The findings indicate that ethicality and coherence emerged as the strongest dimensions shaping teachers’ acceptability of curriculum change, whereas the opportunity dimension did not load onto the acceptability construct. A statistically significant but weak relationship was identified between teaching experience and teacher acceptability. These results suggest that curriculum implementation is influenced not only by individual teachers but also by broader systemic factors, including school leadership, parents, government policy, and the broader context. This study extends the application of Sekhon’s acceptability framework beyond healthcare by adapting it to curriculum evaluation in education. It offers a novel psychological perspective on teachers as active agents in curriculum change and contributes an empirically grounded model of acceptability that supports process-oriented and context-sensitive curriculum evaluation. Keywords: acceptance, curriculum evaluation, elementary school teachers, mutually adaptive.